COOPERATIVES IN THE ERA OF DIGITALIZATION FROM THE PERSPECTIVE OF INNOVATION DIFFUSION THEORY AT THE CU SEHATI COOPERATIVE IN JAKARTA - Dwi Kartikawati; Nurhasanah (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
This research discusses the change of cooperatives towards digitalization from the perspective of Innovation Diffusion theory from Everett M Rogers at the CU Sehati Cooperative in Jakarta. Digitalization is an important strategy for cooperatives to continue to exist and be relevant during such rapid technological changes. This study uses a qualitative-descriptive approach with case study and literature study methods. The study results show that the implementation of digitalization in the CU Sehati Cooperative is in the innovation stage, with cooperative members as adopters who support the organization's sustainability. The study identifies the key factors influencing technology adoption. It also recommends training cooperative members and strengthening digital infrastructure to accelerate technology adoption so that cooperatives can increasingly contribute to the community's economy.